2023
DOI: 10.11646/zootaxa.5369.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Two new species of Lepidocyrtus (Fractocyrtus) Cipola & Bellini (Collembola, Entomobryidae, Lepidocyrtinae), with new records and a new name for Lepidocyrtus (F.) americanus Cipola & Bellini, 2018

NIKOLAS GIOIA CIPOLA,
STÉPHANIE DOS SANTOS VIANA

Abstract: Herein we propose a new name, Lepidocyrtus (Fractocyrtus) amazonaensis nom. nov. Cipola, to replace L. americanus Cipola & Bellini 2018, a combination preoccupied by Marlatt (1896). In addition to new geographic records for the species, two new species of Fractocyrtus are described: L. (Fractocyrtus) andensis sp. nov. from the Colombian Andes and L. (Fractocyrtus) chicomendesi sp. nov. from the Occidental Brazilian Amazon. The new species differs from other members of the subgenus in body color, dorsal cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…A recent survey conducted in Amazonas state revealed that municipalities with large territories, such as São Gabriel da Cachoeira (SGC), remain under-sampled taxonomically, making these areas a priority for Odonata research (Koroiva et al, 2020). SGC, also known as "Cabeça do Cachorro" ("Dog's Head"), located in the extreme northwest of Brazil, stands out by its high biodiversity, as is observed in various groups of animals (Cipola & Viana, 2023;Hamada et al, 2006;Lourenço, 2005;Nogueira et al, 2014). Therefore, it is reasonable to presume that numerous species are yet to be discovered, and that some have not yet been adequately documented from the state of Amazonas or Brazil in general.…”
Section: Introductionmentioning
confidence: 99%
“…A recent survey conducted in Amazonas state revealed that municipalities with large territories, such as São Gabriel da Cachoeira (SGC), remain under-sampled taxonomically, making these areas a priority for Odonata research (Koroiva et al, 2020). SGC, also known as "Cabeça do Cachorro" ("Dog's Head"), located in the extreme northwest of Brazil, stands out by its high biodiversity, as is observed in various groups of animals (Cipola & Viana, 2023;Hamada et al, 2006;Lourenço, 2005;Nogueira et al, 2014). Therefore, it is reasonable to presume that numerous species are yet to be discovered, and that some have not yet been adequately documented from the state of Amazonas or Brazil in general.…”
Section: Introductionmentioning
confidence: 99%